Mechanical Properties of Shale-Reservoir Rocks Based on Stress–Strain Curves and Mineral Content - Wen-Tie Sun; Zhong-Hui Li; Yi-Shan Lou; Liang Zhu; Hui-Mei Wu; Arnaud Regis Kamgue Lenwoue; Qin Liu (Geofluids, 2022)
The evaluation of rock mechanic characteristics of shale reservoir is the key for the success of fracturing. Several limitations such as complex lithology can affect the accuracy of the rock mechanic property computation. In this research, the mechanical rock properties of shale reservoirs were analyzed based on experimental tests including shale-reservoir mineral composition, uniaxial compressive strength, and triaxial compression tests. The results showed that (1) the difference in mineral composition leads to easier fracturing of sand shale reservoirs compared with pure shale reservoir. (2) Under uniaxial conditions, the rock mechanical parameters along the vertical bedding direction of sand shale reservoirs are better than pure shale reservoir parameters. The mechanical properties of shale reservoirs in parallel bedding direction are less affected by lithology. Under triaxial conditions, the confining pressure increases more than 4.0 times with the compressive strength of rocks, and the rock Young’s modulus in the parallel bedding direction is higher compared with the vertical bedding direction. (3) Rock failure mode is mainly subdivided into cutting and splitting modes, and the bedding features of rock mechanic properties highly influence the drilling and fracturing operations. This study offers guidelines for the optimization of the drilling and fracturing process based on accurate evaluation of the rock mechanical properties.